Gerakan Masyarakat Peduli Remaja (GEMPAR) di Desa Petungsewu, Dau, Kabupaten Malang - Lisa Purbawaning Wulandari; Rita Yulifah (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Adolescence is the starting point of the human life cycle in preparing for a healthy reproductive process. Based on RPJMN 2016 data for East Java, it was found that problems related to adolescents include knowledge of Adolescent Reproductive Health (KRR) in East Java which is still low, this is indicated by the Adolescent Knowledge Index about KRR is still low at 55.3%. The Community Service, which was held in Petungsewu Village, Dau District, aims to increase adolescent knowledge about reproductive health, increase cadre knowledge about youth KMS and be skilled in carrying out youth posyandu activities. The method used in this activity is the provision of education using ppt media, videos and booklets. The participants were 20 youths and 10 youth cadres. The activity continued with the implementation of the Youth Posyandu. The results of educational activities showed that the level of knowledge of adolescents about reproductive health increased from 35% to 75% with good knowledge and cadres were able to carry out Youth Posyandu with assistance. ABSTRAK Remaja merupakan titik awal siklus kehidupan manusia dalam mempersiapkan proses reproduksi yang sehat. Berdasarkan data RPJMN 2016 Jawa Timur menemukan problematika yang berhubungan dengan remaja antara lain pengetahuan Kesehatan Reproduksi Remaja (KRR) di Jatim masih rendah, hal ini ditandai dengan Indeks Pengetahuan Remaja tentang KRR masih rendah yaitu sebesar 55,3%. Pengabdian Masyarakat yang dilaksanakan di Desa Petungsewu Kecamatan Dau ini bertujuan untuk meningkatkan pengetahuan remaja tentang kesehatan reproduksi, meningkatkan pengetahuan kader tentang KMS remaja dan terampil dalam melaksanakan kegiatan posyandu remaja. Metode yang dilakukan dalam kegiatan ini adalah pemberian edukasi menggunakan media ppt, video dan booklet. Peserta adalah remaja sejumlah 20 remaja dan 10 kader remaja. Kegiatan dilanjutkan dengan pelaksanaan Posyandu Remaja. Hasil kegiatan edukasi menunjukan tingkat pengetahuan remaja tentang kesehatan reproduksi meningkat dari 35% menjadi 75% berpengetahuan baik dan kader mampu melaksanakan posyandu remaja dengan pendampingan.